Ta’wil Muḥammad Syaḥrūr atas Al-Qur’ān - Reni Nur Aniroh (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2016)
This article examines the thinking of Muḥammad Syaḥrūr, especially on the ta’wil methodology. In this case, ta‘wil as one method to uncover the mystery and tremendous potential in the Qur‘an (especially mutashabihat verses), still holds endless polemics up to now. On the one side, this method is applied rigorously, moreover regarded as something bad. On the other side, some people applying this method are too easy and ever ignore the structure of the text and give priority for interpreter intuitive awareness. The activity of ta’wil only brings verses to soar metaphysical reality and not much in giving the social problems solving. However, in this study, I will introduce the methodology of ta‘wil by Muḥammad Syaḥrūr, using the historis-philosophical and hermeneutical approach. For him, ta’wil is not only bring verses in the metaphysical region, but also the empirical reality of the region, that is not done by many interpreter generally.